Phosphorylated ribosomal S6 (p-rpS6) as a post-treatment indicator of HER2 signalling targeted drug resistance. (July 2015) - Yang-Kolodji, Gloria; Mumenthaler, Shannon M.; Mehta, Arjun; Ji, Lingyun; Tripathy, Debu
Abstract Objective: To identify clinically relevant predictive biomarkers of trastuzumab resistance. Material and methods: MTT, FACS assays, immunoblotting and immunocytochemistry were used to phenotypically characterize drug responses of two cell models BT474R and SKBR3R. Student's t-test and Spearman's correlation were applied for statistic analysis. Results: The activity of a downstream effector of the HER2 pathway phosphorylated ribosomal protein S6 (p-rpS6), was suppressed by trastuzumab in the parental cell lines yet remained unchanged in the resistant cells following treatment. The level of p-rpS6 was inversely correlated to the drug induced growth inhibition of trastuzumab-resistant cells when they are treated with selected HER2 targeting drugs. Conclusion: p-rpS6 is a robust post-treatment indicator of HER2 pathway-targeted therapy resistance.